Adsorption of Uranyl Ion onto Peat with Pseudo-Second-Order Kinetic Models - Liu, Zhi-Rong; Zhou, Shao-Qi (Asian Journal of Chemistry, 2012)
Kinetic experiments were carried out to investigate the effects of pH and initial uranyl ions concentration on the adsorption capability of peat by batch tests. Both the regression coefficient and the deviation of adsorption capacity at equilibrium were employed as error analysis methods to determine the best-fitting kinetic model. The results indicate that the adsorption process can be described by type 1 of the pseudo-second-order kinetic model excellently by linear regression method when compared to other type of the pseudo-second-order kinetic model.